EFFECTS OF CARDIOVASCULAR CONDITIONING EXERCISES ON QUALITY OF LIFE IN PATIENTS WITH DILATED CARDIOMYOPATHY IN PAKISTAN - Murad, Saba; Siddiqi, Furqan Ahmed; Tariq, Muhammad Iqbal; Butt, Mehwish Waseem (Journal of Ayub Medical College Abbottabad, 2019)
Background: Dilated Cardiomyopathy (DCM) is the most frequently diagnosed cardiomyopathy in Pakistan and patients have significant muscles dysfunction which affects their quality of life (QOL). Available evidence have supported the role of moderate intensity exercise for improving QOL but no such studies have been conducted in Pakistan so far. Methods: A single blinded randomized controlled trial was conducted in two different hospitals of Rawalpindi from September 2016-February 2017. Both genders clinically stable DCM patients with ejection fraction <40% were selected through purposive non-probability sampling and randomized to Training group and Control group (n=30 each). Training group protocol included bicycling on lower limb ergometer 4days/week on alternate days for 8 weeks. Patients in control group received usual care. Patients were assessed thrice during 8-week protocol. The tools used included structured questionnaire with different standard scales like 6 Minute Walk Test, Modified Medical Research Council Scale, Modified Borg Scale and Minnesota Living with Heart Failure Questionnaire. Data was analysed on SPSS 21 software. Results: Prior to conditioning in training group, 6 (21%) patients reported good and 23 (79%) have poor QOL whereas in control group 14 (56%) have good and 11 (44%) have poor QOL on MLHFQ score. After 8 weeks in training group, 28 (96%) patients reported excellent QOL and in control group, 11 (44%) reported good and 14(56%) have poor QOL on MLHFQ score. Between the groups analysis depicted highly significant p values for QOL and New York Heart Association (NYHA) class (p<0.001). Conclusion: Supervised cardiac conditioning program significantly improves Quality of life and NYHA functional class in dilated cardiomyopathy. Keywords: Cardiac rehabilitation; Dilated cardiomyopathy; Exercise; Minnesota Living with Heart Failure; Quality of life; NYHA